Data collection and analysis - Sapsford, Roger; Jupp, Victor; Open University (London ; Thousand Oaks, [Calif.] : SAGE, 2006)
This work illustrates the range of techniques used in social research projects and considers the structure and logic of projects as well as the ethics and politics of research. This edition has new chapters on researching via the Internet and up-to-date examples of research in action.
Published in association with The Open University.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Statistical methods; Social sciences -- Research